Association between echocardiographic structural parameters and body weight in Wistar rats - Oliveira-Junior, Silvio A.; Martinez, Paula F.; Fan, William Y.C. [UNESP]; Nakatani, Bruno T. [UNESP]; Pagan, Luana U. [UNESP]; Padovani, Carlos R. [UNESP]; Cicogna, Antonio C. [UNESP]; Okoshi, Marina P. [UNESP]; Okoshi, Katashi [UNESP] (Impact Journals, 2017)
Background: The association between echocardiographic structural parameters and body weight (BW) during rat development has been poorly addressed. We evaluated echocardiographic variables: left ventricular (LV) end-diastolic (LVDD) and end-systolic (LVSD) diameters, LV diastolic posterior wall thickness (PWT), left atrial diameter (LA), and aortic diameter (AO) in function of BW during development. Results/Materials and Methods: Male Wistar rats (n = 328, BW: 302-702 g) were retrospectively used to construct regression models and 95% confidence intervals relating to cardiac structural parameters and BW. Adjusted indexes were significant to all relationships; the regression model for predicting LVDD (R2 = 0.678; p < 0.001) and AO (R2 = 0.567; p < 0.001) had the highest prediction coefficients and LA function the lowest prediction coefficient (R2 = 0.274; p < 0.01). These relationships underwent validation by performing echocardiograms on additional rats (n = 43, BW: 300-600 g) and testing whether results were within confidence intervals of our regressions. Prediction models for AO and LA correctly allocated 38 (88.4%) and 39 rats (90.7%), respectively, within the 95% confidence intervals. Regression models for LVDD, LVSD, and PWT included 27 (62.7%), 30 (69.8%), and 19 (44.2%) animals, respectively, within the 95% confidence intervals. Conclusions: Increase in cardiac structures is associated with BW gain during rat growth. LA and AO can be correctly predicted using regression models; prediction of PWT and LV diameters is not accurate.
Keywords: Cardiac structures; Development; Echocardiogram; Physiological cardiac remodeling; Rat